Endoscopic management of familial adenomatous polyposis in patients refusing colectomy - Ishikawa, Hideki; Mutoh, Michihiro; Iwama, Takeo; Suzuki, Sadao; Abe, Takashi; Takeuchi, Yoji; Nakamura, Tomiyo; Ezoe, Yasumasa; Fujii, Gen; Wakabayashi, Keiji; Nakajima, Takeshi; Sakai, Toshiyuki (Endoscopy, 2016)
Background and study aims: Colectomy protects against colorectal cancer in familial adenomatous polyposis (FAP); however, some patients with FAP refuse surgery. The aim of this study was to evaluate the feasibility and safety of endoscopic management of these patients.Patients and methods: A retrospective review of medical records was performed to identify adult patients with FAP who refused colectomy and were managed by repeated colonoscopies to remove numerous polyps between 2001 and 2012. Polyps were removed by hot snare polypectomy or endoscopic mucosal resection. Polyps of < 10 mm in size and without endoscopic features suggesting cancer were discarded without histological examination; the remaining polyps were examined histologically.Results: Of the 95 eligible patients, five (5.3 %) were excluded. The remaining 90 patients (median age at first visit 29 years [range 16 – 68 years]; 46 males) were followed for a median of 5.1 years (interquartile range [IQR] 3.3 – 7.3 years). During this period, a total of 55 701 polyps were resected without adverse events such as bleeding or perforation. The median numbers of endoscopic treatment sessions and polyps removed per patient were 8 (IQR 6 – 11) and 475 (IQR 211 – 945), respectively. Five patients had noninvasive carcinoma (Category 4.2 according to the revised Vienna classification), detected within 10 months from the start of the follow-up period. All of these patients were treated endoscopically, without signs of recurrence during a median follow-up of 4.3 years (IQR 2.0 – 7.1 years). No invasive colorectal cancer was recorded during the study period. Two patients (2.2 %) underwent colectomy because the polyposis phenotype had changed to dense polyposis. Conclusion: Endoscopic management of FAP is feasible and safe in the medium term.